Reconstruction of recycling flux from synthetic camera images, evaluated for the Wendelstein 7-X startup limiter. (22nd September 2017) - Frerichs, H.; Effenberg, F.; Feng, Y.; Schmitz, O.; Stephey, L.; Reiter, D.; Börner, P.
Abstract: The interpretation of spectroscopic measurements in the edge region of high-temperature plasmas can be guided by modeling with the EMC3-EIRENE code. A versatile synthetic diagnostic module, initially developed for the generation of synthetic camera images, has been extended for the evaluation of the inverse problem in which the observable photon flux is related back to the originating particle flux (recycling). An application of this synthetic diagnostic to the startup phase (inboard) limiter in Wendelstein 7-X (W7-X) is presented, and reconstruction of recycling from synthetic observation of H α emission is evaluated. It is shown that recycling—in terms of re-ionization within the view cone of the camera—is underestimated by a factor of about 3 at the peak location and overestimated in between, and that H α emission related to molecular dissociation can locally yield an additional factor of 2 for the ionization to photon conversion. Fitted conversion factors are extracted from the simulation results which include a dependence on the plasma density.